2006
DOI: 10.1111/j.1440-1746.2005.04148.x
|View full text |Cite
|
Sign up to set email alerts
|

γδ T cells increase with gastric mucosal interleukin (IL)‐7, IL‐1β, and Helicobacter pylori urease specific immunoglobulin levels via CCR2 upregulation in Helicobacter pylori gastritis

Abstract: Gastric mucosal increases in IL-7 and IL-1beta closely corresponded to the accumulation of gammadelta T cells in gastric mucosa. An association was also seen between gammadelta T cell accumulation and H. pylori urease-specific Ig levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
3
10
0
1
Order By: Relevance
“…Smad3 negatively regulates Th17 cell development through FoxP3 (Lu et al, 2010; Tone et al, 2008). In agreement with prior studies (Futagami et al, 2006; Lee et al, 2012; Lundgren et al, 2005), gastric T-reg and Th17 cell response-related genes (e.g., STAT3, Ccr2, Tgfb) were differentially expressed in response to H. pylori (Supplemental File 1). However, we also observed modestly higher levels of Th17 cells and a trend towards more T-reg cells in pulmonary tissues of H. pylori -infected mice, with effects enhanced in the cohort infected at a younger age.…”
Section: Discussionsupporting
confidence: 90%
“…Smad3 negatively regulates Th17 cell development through FoxP3 (Lu et al, 2010; Tone et al, 2008). In agreement with prior studies (Futagami et al, 2006; Lee et al, 2012; Lundgren et al, 2005), gastric T-reg and Th17 cell response-related genes (e.g., STAT3, Ccr2, Tgfb) were differentially expressed in response to H. pylori (Supplemental File 1). However, we also observed modestly higher levels of Th17 cells and a trend towards more T-reg cells in pulmonary tissues of H. pylori -infected mice, with effects enhanced in the cohort infected at a younger age.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we found that infection with the enteric rodent pathogen C. rodentium promoted IL-7 production from IECs, in agreement with a published study suggesting that H. pylori infection causes increased intestinal IL-7 in humans (32). Therefore, intestinal epithelium-derived IL-7 may be one of the important molecules that inhibit inflammation and infection caused by various bacteria.…”
Section: Discussionsupporting
confidence: 79%
“…We here evidenced an over production of IL-7 during the first days of acute SIV infection, especially within the small intestine, which may participate to the characteristic cytokine storm occurring during the acute phase of SIV/HIV infection (21). Interestingly, similar enhancements of local IL-7 expression were recently observed in mice infected with C. rodentium , and in humans infected with Helicobacter pylori (23, 43). Earlier and stronger viral infection in the ileum compared to LNs or to other parts of the gut suggests that the presence of infected cells directly triggers local IL-7 production.…”
Section: Discussionsupporting
confidence: 78%